Efficacy and safety of nonsteroidal mineralocorticoid receptor antagonists for renal and cardiovascular outcomes in patients with chronic kidney disease: a meta-analysis of randomized clinical trials - Chen, Qianlan; Wei, Guocui; Wang, Yanping; Li, Xiuxia; Zhao, Qian; Zhu, Ling; Xiao, Qing; Xiong, Xuan (Frontiers in Pharmacology, 2024)
Objective: To systematically review the efficacy and safety of nonsteroidal mineralocorticoid receptor antagonists (MRAs) in chronic kidney disease (CKD).We systematically searched six databases to identify randomized controlled trials (RCTs) about nonsteroidal MRAs for CKD, from inception to August 22, 2023. Two reviewers independently screened the retrieved articles, extracted data, and assessed the risk of bias of included RCTs using the Cochrane risk of bias tool. We then conducted meta-analysis of the data using Stata 17.0 software.Results: 11 RCTs (n= 15,817) were included in this meta-analysis. Compared with placebo, nonsteroidal MRAs significantly reduced the proportion of patients with ≥40% decline in estimated glomerular filtration rate (eGFR) from baseline (RR=0.85, 95% CI [0.78, 0.92], P<0.001), although the magnitude of eGFR reduction was greater (WMD=-2.83, 95% CI [-3.95, -1.72], P<0.001). The experimental group also had lower incidence of composite renal outcome (RR=0.86, 95% CI [0.79, 0.93], P<0.001) and greater reduction in urine albumin-to-creatinine ratio (UACR) from baseline (WMD=-0.41, 95% CI [-0.49, -0.32], P<0.001), as well as reduced cardiovascular events (RR =0.88, 95% CI [0.80, 0.95], P =0.003). MRAs did not increase any adverse events compared to placebo (RR=1.00, 95% CI [0.99, 1.01], P =0.909), but had higher incidence of hyperkalemia (RR=2.05, 95% CI [1.85, 2.28], P<0.001). Compared with eplerenone, there was no significant difference in the proportion of patients with ≥40% decline in eGFR (RR=0.57, 95% CI [0.18, 1.79], P=0.335) or hyperkalemia (RR=0.95, 95%CI [0.48, 1.88], P=0.875).Nonsteroidal MRAs can reduce the incidence of end-stage renal disease and cardiovascular adverse events in patients. Although there was still a risk of hyperkalemia compared to placebo, there was no significant difference in any adverse events compared to either placebo or eplerenone. It has become a new option for drug treatment of CKD patients, but more clinical trials are still needed to verify its efficacy and safety. Especially further direct comparison of the nonsteroidal MRAs to eplerenone in view of the relatively small number of patients reviewed are needed.